Various fatal complications of urolithiasis - Hájková, Veronika; Švecová, Tereza; Uvíra, Matěj; Vojtíšek, Tomáš; Handlos, Petr (Forensic science, medicine, and pathology, 2021)
This article describes two cases of fatal complications of urolithiasis. The first case discusses the development of fatal urosepsis in a patient with a known mental health issue. The patient had self-introduced a thermometer into her bladder, which led to stone formation around the thermometer and consequently to fatal urosepsis. The second case deals with a motor vehicle accident in which a passenger with pre-existing hydronephrosis suffered a kidney injury leading to fatal bleeding into the surrounding adipose tissue. To provide a wider context, the paper also discusses the fatal complications and origin of urolithiasis.
Keywords: Kidney; sepse; Sepsis; lidé; Female; Urolithiasis; Hydronephrosis; ledviny; Cause of death; Trauma; Urosepsis; ženské pohlaví; urolitiáza; Humans